1998
DOI: 10.1002/(sici)1521-4125(199801)21:1<71::aid-ceat71>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Various Admixtures on the Calcium Carbonate Precipitation from a Calcium Nitrate and Monoethanolamine Solution

Abstract: Calcium carbonate was precipitated by carbonation of calcium nitrate and monoethanolamine solution. The influence of various organic admixtures on the crystallization, crystal morphology, and polymorphism of calcium carbonate has been studied using different techniques. Our results show that sucrose and fructose present even at very high concentrations do not affect the duration or mechanism of the carbonation process at a higher degree, what is attributed to the specific quality of the ethanolamine process. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Also, an increase in the concentration of calcite in PCC on the surface of used polyelectrolyte films was observed [28]. However, almost no effect of fructose and sucrose on calcite characteristics was observed when precipitation was carried out in the gas-liquid system by the ethanolamine process [31] or in the gas-slurry system using calcium hydroxide as a substrate [32], but a higher degree of particles agglomeration in both studies was observed.…”
Section: Introductionmentioning
confidence: 89%
“…Also, an increase in the concentration of calcite in PCC on the surface of used polyelectrolyte films was observed [28]. However, almost no effect of fructose and sucrose on calcite characteristics was observed when precipitation was carried out in the gas-liquid system by the ethanolamine process [31] or in the gas-slurry system using calcium hydroxide as a substrate [32], but a higher degree of particles agglomeration in both studies was observed.…”
Section: Introductionmentioning
confidence: 89%